Validity of the telematic Fugl Meyer assessment scale – upper extremity (TFMA-UE) Spanish version - Llamas-Ramos, Rocío; Llamas-Ramos, Inés; Pérez-Robledo, Fátima; Sánchez-González, Juan Luis; Bermejo-Gil, Beatriz María; Frutos-Bernal, Elisa; Martín-Nogueras, Ana María (Frontiers in Neurology, 2023)
Background Telematic assistance has become indispensable in recent years. The increased prevalence of Acquired brain injury and the sequels it causes, requires long–lasting multidisciplinary treatments. Validated tools to assess the evolution of the disabilities and limitations of this pathology are essential to individualize and prescribe adapted treatments. The aim has been to create the telematic version of the Fugl Meyer Assessment-Upper Extremity Motor Function (TFMA-UE) Spanish scale and its adaptation to the remote assessment of neurologic patients. Methods An adapted scale was designed based on the Fugl Meyer Assessment scale-telematic version (FMA-TV): TFMA-UE. This scale is composed by 21 items which evaluate the upper extremity motor function. Physiotherapists trained in this tool, evaluate the results obtained from applying the two versions (on-site and telematic) to compare the results. Results TFMA-UE was administered to 30 patients with acquired brain injury. It was applied on site and through the web platform selected by the patients in two different days. Patients completed all the scale in an easily way without help. The exploratory and confirmatory factor analysis confirmed a factorial structure with a factor (76.08% of the variance). The Cronbach’s internal consistency index obtained was 0.98 and the weight kappa index used to measure agreement between the two versions was 0.78 which represents substantial agreement. Conclusion The Telematic Fugl Meyer Assessment-Upper Extremity Motor Function (TFMA-UE) scale is a viable, useful and easy to apply tool that allows the upper extremity motor function assessment of Acquired Brain Injury patients.